Psychological vulnerability and well-being of Chinese international students in Southeast Asia’s EMI contexts: A systematic review - Xue, Wenou (Journal of International Students, 2026)
The rapid increase in the number of Chinese international students in English–medium instruction programs in Southeast Asia has raised concerns about their psychological well-being. Despite growing scholarly attention to international student mental health, a comprehensive, region-specific synthesis for Southeast Asia remains lacking. This review examined empirical studies published between 2015 and 2025 on psychological outcomes, acculturative stress, and well-being among Chinese students in Southeast Asian higher education. Drawing on Berry’s acculturation theory and Lazarus and Folkman’s coping framework, this review identified recurring stressors, including English communication anxiety, localized challenges in English comprehension, heavy academic workloads, and cultural expectations related to religion, food, and gender norms. Protective factors such as social and family support, resilience, and self-efficacy reduce stress, whereas avoidance coping intensifies it. Methodological limitations included reliance on cross-sectional surveys, inconsistent adaptation of measurement instruments, and limited theoretical integration.